1994
DOI: 10.1152/jappl.1994.76.2.539
|View full text |Cite
|
Sign up to set email alerts
|

Role of high-frequency ventilation in surfactant-depleted lung injury as measured by granulocytes

Abstract: Granulocytes were collected from the lung lavage fluid of surfactant-depleted rabbits to assess the relationship between granulocyte-related lung injury and ventilatory mode. The number of lavaged granulocytes was determined after 2 and 4 h of conventional mechanical ventilation (2CMV and 4CMV, respectively) or high-frequency oscillatory ventilation (2HFO and 4HFO, respectively). Stimulated respiratory bursts were assayed by luminol-dependent chemiluminescence (LDCL) with N-formyl-methionyl-leucyl-phenylalanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 0 publications
7
29
0
Order By: Relevance
“…The activity of surfactant is improved when hydrophobic surfactant proteins are constituents of the surfactant [109], whereas positive end-expiratory pressure (PEEP) improved the response to supplied surfactant [265,277,284]. The application of high frequency oscillatory ventilation may be useful for the prevention of lung injury (especially air leak syndrome) [125,142,203] and does not alter the turnover of surfactant [340]. In animal experiments it has been demonstrated that intraamniotic surfactant is taken up from the amniotic fluid [89].…”
Section: Therapeutic Use Of Surfactantmentioning
confidence: 99%
“…The activity of surfactant is improved when hydrophobic surfactant proteins are constituents of the surfactant [109], whereas positive end-expiratory pressure (PEEP) improved the response to supplied surfactant [265,277,284]. The application of high frequency oscillatory ventilation may be useful for the prevention of lung injury (especially air leak syndrome) [125,142,203] and does not alter the turnover of surfactant [340]. In animal experiments it has been demonstrated that intraamniotic surfactant is taken up from the amniotic fluid [89].…”
Section: Therapeutic Use Of Surfactantmentioning
confidence: 99%
“…Mean airway pressure was set initially 0.3 kPa (3 cm H 2 O) higher than during conventional ventilation. Airway pressure was increased every 10-15 min in increments of 0.1 to 0.2 kPa (1-2 cm H 2 O) until a Pa,o 2 of 1 53 kPa (400 mm Hg), an 'optimized' value taken from the literature [17,20,21,25]. Oscillatory frequency was maintained at 10 Hz.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Indeed, repeated saline lung lavage yields a widely accepted animal model of respiratory insufficiency suitable for the evaluation of respiratory therapeutics [19]. The study design looks much like previously published studies evaluating the short term effects of HFOV [17,20,21] and PLV [3]. Our protocol, however, prescribed adjustment of ventilator settings as clinically indicated in all study groups.…”
Section: Introductionmentioning
confidence: 99%
“…Maintenance of pulmonary volume avoids pulmonary overdistension as well as occurrence of atelectasia in patients with ARDS and the flow standard may improve in relation to ventilation-perfusion. (11,12) Successful treatment of ARDS requires a strategy to keep the lungs open, the open lung approach. Recruitment of collapsed alveoli reduces intrapulmonary shunt, reducing the fraction of inspired oxygen (FiO 2 ) to less toxic concentrations.…”
Section: Clinical Aplications Of Hfov In Pe-diatricsmentioning
confidence: 99%
“…This ventilation mode has been successfully used to treat patients with severe respiratory failure when CMV fails, Furthermore, reports state that when HFOV is used earlier, together with a protective strategy, a decrease of the acute or chronic pulmonary injury occurs in patients with ARDS. (5,10,11) The 3100A by SensorMedics® ventilator is approved by Food and Drug Administration (FDA) for use in children up to 35 kg. This is a device for mechanical pulmonary ventilation with a continuous flow of gas capable of eliminating CO 2 and keeping airway pressure constant.…”
Section: Introductionmentioning
confidence: 99%